Diz-me com quem andas... intertexto e intertextualidade : uma leitura do romance Borges e os orangotangos eternos de Luis Fernando Veríssimo - Magalhães Filho, José Soares de (2009)
Intertext is the subject that leads this research. A proposition for the notion is made, in opposition to the ideia of intertextuality. Propositions for the two notions are pointed, revealing that the concepts are not so easily placed. Freudian theory of remembrance process is used to question the authorship. It proposes teh concept of the intertext as memory for literature. On a second level, the basis of detective story as a narrative genre is approached historically, its origins localized in Edgar Allan Poe‘s 19th century, a time of positivist ideas, throwing a look at the american noir novels and its influence over brazilian detective stories. Borges e os orangotangos eternos (2002), a novel by Luis Fernando Verissimo is analized enphfasising on the intertexts. The novel has argentinean novelist Jorge Luis Borges as a central charachter and brings his most notorious themes, general references to general literature and to detective stories, as well as to the author‘s process of making literature. It proposes the intertext as an influence to the subject, as well as a means of looking for the ideological intentions brought by a text.